Governance of global climate change in the Brazilian Amazon: the case of Amazonian municipalities of Brazil - Inoue,Cristina (2012)
With regards to the debate about governance of climate change, it should be assumed that the Amazon region plays an important role, as this large area is highly vulnerable to its effects. In this sense, this article aims to discuss how some Amazonian municipalities of Brazil have been taking part in the complexes and multilayered processes of climate governance.